2015
DOI: 10.7600/jpfsm.4.117
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of eccentric contraction induces alterations in <i>in vitro</i> sarcoplasmic reticulum Ca<sup>2+</sup> handling in rat hindlimb muscles

Abstract: In order to investigate factors that contribute to eccentric contraction (ECC)-induced loss of tetanic force, Ca 2+ uptake, Ca 2+ release, and Ca 2+ -ATPase activity of the sarcoplasmic reticulum (SR) and sarcolemmal Na + -K + -ATPase activity were examined in rat fast-twitch skeletal muscles that underwent in situ ECC or isometric contraction (ISC) for up to 500 repetitions. The tetanic force at 60 Hz was more depressed in ECC-treated muscles than in ISC-treated muscles. SR Ca 2+ -ATPase activity displayed bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…ECC results in an inability to produce the desired force characterized by triad deformation [36], sarcomere inhomogeneity [37], increased membrane permeability [38], inflammation [39], and proteolysis [21] release rate in rat fast-twitch muscles. We noted that loss of ECC-induced contractile activity can be attributed to a failure of SR Ca 2+ release [11]. Nitrate ingestion enhanced SR Ca 2+ release and tetanic force production via modifications of the cellular Ca 2+ handling components in mouse fast-twitch muscle [20].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…ECC results in an inability to produce the desired force characterized by triad deformation [36], sarcomere inhomogeneity [37], increased membrane permeability [38], inflammation [39], and proteolysis [21] release rate in rat fast-twitch muscles. We noted that loss of ECC-induced contractile activity can be attributed to a failure of SR Ca 2+ release [11]. Nitrate ingestion enhanced SR Ca 2+ release and tetanic force production via modifications of the cellular Ca 2+ handling components in mouse fast-twitch muscle [20].…”
Section: Discussionmentioning
confidence: 83%
“…Throughout the experiment, the rats were deeply anesthetized with an intraperitoneal injection of a mixture of medetomidine (0.4 mg kg body wt −1 ), midazolam (2.0 mg kg body wt −1 ), and butorphanol (2.5 mg kg body wt −1 ). ECC was performed as described previously [11]. Briefly, an animal was placed in the supine position on a supporting platform, with the left foot secured in a foot holder attached to the rim of a servomotor.…”
Section: Exercise Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…This is primarily due to muscle damage, characterized by swelling 2) , inflammation 3) , triad deformation 4,5) , increased membrane permeability 6) , proteolysis 7) , or a combination of these. It has been suggested that sarcomeres within myofibrils, transverse tubules, and the sarcoplasmic reticulum (SR) are susceptible to damage in overstretched regions, which may be the basis of impairment to excitation-contraction coupling 8) .…”
Section: Introductionmentioning
confidence: 99%